Hubungan Sumber Daya dan Struktur Birokrasi Protokol Kesehatan Terhadap Persepsi Penurunan Angka Kejadian Covid-19 - Dewi Sayati; Atma Deviliawati; Hamyatri Rawalillah (Institut Citra Internasional, 2023)
The increase in the number of cases of COVID-19 is still happening every day, therefore, a very comprehensive effort is needed in managing the Covid-19 case and ways to break the chain of exposure. Based on data from the Covid-19 Handling Task Force as of March 31, 2022 globally, the total number of Covid-19 infections was 486,661,998 cases,active cases of covid-19 as many as 58,643,881 cases,and the death rate reached 6,161,174 people.This study aims to find out the relationship between resources and bureaucratic structure with the perception of a decrease in the number of Covid-19 cases at Bina Jaya Vocational School in 2022. The design of this study is descriptive analytic, using a cross sectional approach. The sample of this research is 71 respondents at SMK Bina Jaya Palembang, and the sampling technique uses accidental sampling. Resources are urgently needed to support the implementation, such as human resources who are actively involved in the policy process, the availability of facilities to support the policies that have been set, unitary system that gives centralized resources of authority to the national government as well as the bureaucratic structure including the dimensions of fragmentation and SOPs which have a significant influence on the success of policy implementation, such as inter-organizational relations as contingency theory, as case analysis, chart of public sector policy and management subsystems.